Stereoselective synthesis of 3-alkylidene/alkylazetidin-2-ones from azetidin-2,3-diones - Tiwari, Dharmendra Kumar; Shaikh, Ashif Y.; Pavase, Laxmikant S.; Gumaste, Vikas K.; Deshmukh, Abdul Rakeeb A. S. (Tetrahedron, 2007)
Azetidin-2,3-diones have been used as synthons for the synthesis of C-3 alkylidene/alkylazetidin-2-ones. Some of the 3-alkylazetidin-2-ones are well known for their cholesterol absorption inhibitor activity. A regio and stereoselective Grignard reaction on a keto group followed by dehydration using PPh3/CCl4 reagent is a key step in this synthesis. Hydrogenation of the 3-alkylideneazetidin-2-ones provided stereoselectively cis-3-alkylazetidin-2-ones in very good yields. (c) 2006 Published by Elsevier Ltd.
Keywords: 3-diones; azetidin-2; azetidin-2-ones; beta-lactam; Grignard reaction

Unlocking thermodynamic enolate for kinetically controlled desymmetrizing vinylogous (4+1) carbospiroannulation - Singh, Sanjay; Singh, Abhijeet; Pandya, Rinu; Vanka, Kumar; Singh, Ravi P. (Chemistry-A European Journal, 2025)
An unprecedented thermodynamically unfavorable (4+1) deysmmetrizing spiroannulation through a thermodynamic enolate intermediate, enabling a single-step synthesis of ubiquitous scaffolds such as all-carbon chiral spirocycles, is disclosed. In this spiroannulation, we present a vinylogous organocatalytic enantioselective desymmetrizing (4+1) cycloaddition approach involving alkylidene malononitrile and cyclopent-1,3-dienone. This carbospiroannulation method produces functionally enriched spiro[4,4]nonane structures with three stereocenters, has presented good-to-high yields and enantiomeric ratios. Detailed DFT calculations reveal an intriguing reaction mechanism, which validates our observations.
Keywords: 3-diones; alkylidene malononitrile; cyclopent-1; quaternary stereocenters; spiro compounds; thermodynamic enolate